2011
DOI: 10.4103/1119-3077.79239
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic childhood coma in Ebonyi State University Teaching Hospital, Abakaliki, South Eastern Nigeria

Abstract: Infections were the predominant causes of non-traumatic coma in EBSUTH. In view of the high mortality among this group of patients, efforts at the control of malaria and other infections would significantly reduce the incidence of non-traumatic coma in this study site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
9
18
0
1
Order By: Relevance
“…Female predominance was seen in study by Ibekwe et [1,3,4,10]. It is also supported by other studies wherein infection of CNS was found to be leading cause of non-traumatic coma [8,9,11,12].…”
Section: Discussionsupporting
confidence: 77%
“…Female predominance was seen in study by Ibekwe et [1,3,4,10]. It is also supported by other studies wherein infection of CNS was found to be leading cause of non-traumatic coma [8,9,11,12].…”
Section: Discussionsupporting
confidence: 77%
“…A study from Iran [8] also reported mortality of 16.6% and sequela of 28.66%. However, a study from Nigeria [9] reported higher mortality of 32.5%. This difference in mortality can be explained by the difference in aetiology, and diagnostic and treatment facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The next common causes of coma were metabolic ones, poisoning, and epilepsy (16). In a retrospective study in Nigeria, the most common causes of non-traumatic coma in 40 children were infectious ones, mostly by cerebral malaria (17). In another study, the most common causes of non-traumatic coma in 100 children were metabolic ones, followed by central nervous system infections and cerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%